PHYSICAL CHARACTERISTICS OF KLAPERTART SUBTITUTION OF SORGUM MILK AS A FUNCTIONAL FOOD - Wika Rinawati, Safa’ah (Prosiding Pendidikan Teknik Boga Busana, 2020)
One way to increase functional food value is to substitute sorghum milk. Sorghum milk is vegetable milk obtained from cereals of sweet sorghum seeds. Sorghum milk as a substitute for animal milk has health benefits, especially for prevention of heart disease, obesity, decreased hypertension, maintaining blood sugar levels, and prevention of colon cancer. In this study using the 4D method (define, design, develop and desseminate), to find the best formula for the comparison of sorghum milk with animal milk in making sorghum milk classifications. The substitutes for sorghum milk that are done are 50%, 75% and 100%. The results of the research showed that the best substitution in the classification of sorghum milk with a percentage of 50% with organoleptic physical characteristics was not much different from the reference, while the results of analysis of nutritional values on substitution of sorghum milk as much as 50% were 70.33% moisture content, 0.48% ash content, fat content 7.08%, protein content 1.03%, crude fiber 0.86%, carbohydrate 21.07%. Keywords: klapertart, sorgum milk , funtional foood